Machine learning models for predicting risks of MACEs for myocardial infarction patients with different VEGFR2 genotypes - Kirdeev, Alexander; Burkin, Konstantin; Vorobev, Anton; Zbirovskaya, Elena; Lifshits, Galina; Nikolaev, Konstantin; Zelenskaya, Elena; Donnikov, Maxim; Kovalenko, Lyudmila; Urvantseva, Irina; Poptsova, Maria (Frontiers in Medicine, 2024)
Background: Development of prognostic models for identification of high-risk myocardial infarction (MI) patients is a crucial step towards personalized medicine. Genetic factors are known to be associated with increased risk of cardiovascular diseases; however, little is known if they can be used to predict major adverse cardiac events (MACEs) for MI patients. This study aims to build a machine learning (ML) model to predict MACEs in MI patients based on clinical, imaging, laboratory and genetic features, and to assess the influence of genetics on the model's prognostic power.We analyzed the data from 218 MI patients admitted to the emergency department at the